Effects of earthworm casts on crop production - Asawalam, D.O.; Hauser, S. (2001)
Greenhouse and field studies were conducted to determine the effect of earthworm casts on the production of maize and cowpea. In pot experiments with mixtures of soil and casts, shoot and root dry matter (OM) of maize and cowpea increased with increasing proportion of casts. Shoot OM of cowpea and root OM of maize increased significantly when worm casts were applied to the soil surface but not when the casts were mixed with the soil. Under field conditions, maize grain yield increased by 73%, 114%, and 180% over the control (without worm casts) when 50 t ha-1, 100 t ha-1, and 150 t ha-1 of casts were applied, respectively. At the 150 t ha-1 rate, a significantly higher maize grain yield was maintained over two cropping seasons. The study demonstrated that earthworm casts are an important resource that can be harnessed for increased crop production.